On Numerical Tracer Advection in the Stratosphere and Assimilation of Data from Satellites - RÖSEVALL, JOHN (2007)
Since the early 1980's, large scale ozone depletion has been observed in the lower regions of the ozone layer over Antarctica when sunlight returns to the polar region in the early spring. The destruction of ozone is attributed to anthropogenic emissions of freon and halon compounds that have augmented the natural stratospheric concentrations of nonreactive Clx and Brx reservoir species with several hundred percent. In the cold Antarctic winter, surface reactions on so called polar stratospheric clouds transform the reservoir species into photoreactive catalysts that destroy ozone when sunlight returns to the polar vortex in the spring.The Arctic polar vortex is less stable and therefore warmer than its southern counterpart. The mixing ratios of photoreactive chlorine and bromine catalysts built up in it during winters are therefore much lower than in the Antarctic vortex. Furthermore, the Arctic polar vortex generally breaks up earlier in the spring which means that there is less time for an ozone hole to form. The destruction of ozone observed in the Arctic lower stratosphere is thus far less severe than in the Antarctic polar vortex.To quantify the loss of polar ozone it is necessary to follow air-masses in the stratosphere so their ozone concentrations can be measured at consecutive times. The objective of this thesis is to demonstrate how polar ozone depletion can be mapped and quantified by assimilating ozone data from satellites into an wind driven off-line transport model. With access to a large set of satellite data, assimilated fields can be built up that are less noisy than the individual satellite ozone profiles. The rates and geographical distribution of ozone de pletion can be determined by comparing the assimilated fields to passively transported fields initialized by assimilation of satellite data. A transport and assimilation model DIAMOND, (Dynamical Isentropic Assimilation Model for OdiN Data) is presented in the thesis. Antarctic as well as Arctic polar ozone destruction is studied by ...